Enhanced photovoltaic performance of benzodithiophene-alt-bis(thiophen-2-yl)quinoxaline polymers via π–bridge engineering for non-fullerene organic solar cells. (24th April 2020) - Tamilavan, Vellaiappillai; Jang, Soyeong; Lee, Jihoon; Agneeswari, Rajalingam; Kwon, Ji Hyeon; Kim, Joo Hyun; Jin, Youngeup; Park, Sung Heum
Abstract: A series of novel alternating polymers, namely P(BDTO-TTFQ), P(BDTT-TTFQ), and P(BDTSi-TTFQ), incorporating electron-rich benzo [1, 2-b:4, 5-bʹ]dithiophene (BDT) derivatives, namely 4, 8-bis(2-butyloctyloxy)benzo [1, 2-b:4, 5-bʹ]dithiophene (BDTO), 4, 8-bis(5-(2-butyloctyl)thiophen-2-yl)benzo [1, 2-b:4, 5-bʹ]dithiophene (BDTT), and 4, 8-bis(triisopropylsilylethynyl)-benzo [1, 2-b:4, 5-ʹ]dithiophene (BDTSi), as well as electron-deficient 5, 8-bis(5-(4-hexylthiophen-2-yl)thiophen-2-yl)-2, 3-didodecyl-6, 7-difluoroquinoxaline (TTFQ) units were prepared. The photo-physical, electrochemical, crystallinity, curvature, charge transport, and photovoltaic properties of the TTFQ-based polymers were investigated thoroughly and compared briefly to those of structurally similar 2, 3-didodecyl-6, 7-difluoro-5, 8-di(thiophen-2-yl)quinoxaline (TFQ)-based polymers, namely P(BDTO-TFQ), P(BDTT-TFQ), and P(BDTSi-TFQ), containing BDTO, BDTT, and BDTSi. This study confirmed that the incorporation of additional π˗bridges (3-hxeylthiophene) between the BDT and TFQ units of P(BDTO-TFQ), P(BDTT-TFQ), and P(BDTSi-TFQ) do not significantly alter the properties of the polymers P(BDTO-TFQ) and P(BDTT-TFQ), but do significantly alter the properties of P(BDTSi-TFQ). Consequently, the polymers P(BDTO-TTFQ) and P(BDTT-TTFQ) exhibit comparable power conversion efficiencies (PCEs, 3.99% and 6.69%, respectively) to those of P(BDTO-TFQ) and P(BDTT-TFQ) (3.49% and 7.06%, respectively), but P(BDTSi-TTFQ) exhibits a significantly improved PCE of 6.21% compared to that of P(BDTSi-TFQ) (0.75%). Graphical abstract: The photovoltaic performance of quinoxaline-based polymers was greatly increased via the side and main chain engineering of the polymer backbone, and the PCE was maximum enhanced from 0.8% to 6.2%. Image 1 Highlights: Qunoxaline-based three new polymers with different substituent were prepared. The calculated optical bands were 1.87 eV, 1.84 eV and 1.85 eV, respectively. The determined HOMO levels were −5.24 eV, −5.36 eV and −5.48 eV, respectively. The maximum PCEs of NFA OSCs were 3.99%, 6.69% and 6.21%. π-bridge engineering on the polymer backbone with were greatly alter their properties.